Arms control policy of the People's Republic of China, 1949-1978 - Hu, Z (1985)
﻿ This study investigates how the PRC, during the three decades since its establishment, has responded to international politics involving arms control and disarmament (ACD) issues, and explores the essence of China's approach to concepts of arms control and disarmament. The central finding is that, despite its seeming relaxation of hostility towards international ACD activities, and the more active and flexible part it has played in them at the UN since the mid-1970s, China remains unconvinced of the value of these activities. This does not make it dangerous, irrational or immature. Chapters Two to Five provide a comprehensive account of the history of Chinese ACD policy between 1949 and 1978. Each chapter represents a distinctive period of Chinese arms control policy. Although more interested in the banning of the use, rather than the possession, of atomic weapons, the PRC behaved at first as an uncritical disciple of Soviet ACD positions (Chapter Two). During the second period (Chapter Three), China became increasingly uneasy about international ACD efforts and began to deviate from the Soviet stance. Moscow's denial of concrete assistance to China's nuclear weapons development, and the conclusion of the Partial Test Ban Treaty, eventually led the PRC into a period (Chapter Four) of open hostility towards nearly all international ACD initiatives. Then, in 1964, China's first nuclear test likewise radically changed its outlook on ACD matters. The final period (Chapter Five) examines its record at the UN in this regard, showing how the PRC was persuaded to commit itself to the Tlatelolco Treaty and to the 1978 UN Special Session on Disarmament. In conclusion, however, there is no evidence to suggest that the PRC has been committed to the concept of a disarmament process through arms control which both the US and the USSR, in their very different ways, have accepted. China has participated in international ACD negotiations while not really believing in their objectives, based as these are on a permanency of two superpowers. It is to be hoped that China's increasing involvement in the UN disarmament negotiation machinery will feed back into PRC policy-making and lead to a more positive and more willing participation in these ACD negotiations.